2011
DOI: 10.1016/j.regsciurbeco.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Human capital, higher education institutions, and quality of life

Abstract: This paper considers the effects of the local human capital level and the presence of higher education institutions on the quality of life in U.S. metropolitan areas. The local human capital level is measured by the share of adults with a college degree, and the relative importance of higher education institutions is measured by the share of the population enrolled in college. This paper finds that quality of life is positively affected by both the local human capital level and the relative importance of highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 48 publications
(52 reference statements)
1
50
0
5
Order By: Relevance
“…QOL has been investigated regarding various life domains, such as residence (Heal and Chadsey-Rusch, 1985;Werner, 2011), neighborhood (Honold et al, 2012;Delmelle et al, 2013), health (De Hollander and Staatsen, 2003;Sturm and Cohen, 2004), education (Frisvold and Golberstein, 2011;Winters, 2011), work (Huang and Sverke, 2007;Tefft, 2012), family life (Greenhaus et al, 2003;Huang and Sverke, 2007), leisure and recreation (Leung and Lee, 2005;Lin et al, 2013), finance (Kaplan et al, 2008), and travel behavior (Abou-Zeid et al, 2012;Cao, 2013;Delmelle et al, 2013). Different life choices are usually decided over different time scales under the influence of limited time and monetary constraints as well as the various needs of households and their members.…”
Section: Decision Boundary Local Decisionmentioning
confidence: 99%
“…QOL has been investigated regarding various life domains, such as residence (Heal and Chadsey-Rusch, 1985;Werner, 2011), neighborhood (Honold et al, 2012;Delmelle et al, 2013), health (De Hollander and Staatsen, 2003;Sturm and Cohen, 2004), education (Frisvold and Golberstein, 2011;Winters, 2011), work (Huang and Sverke, 2007;Tefft, 2012), family life (Greenhaus et al, 2003;Huang and Sverke, 2007), leisure and recreation (Leung and Lee, 2005;Lin et al, 2013), finance (Kaplan et al, 2008), and travel behavior (Abou-Zeid et al, 2012;Cao, 2013;Delmelle et al, 2013). Different life choices are usually decided over different time scales under the influence of limited time and monetary constraints as well as the various needs of households and their members.…”
Section: Decision Boundary Local Decisionmentioning
confidence: 99%
“…These human capital externalities are thought to result for several reasons, including increased technological innovation by the higher educated, knowledge spillovers from highly skilled workers to their neighbors and coworkers, and production complementarities between high-skill and low-skill workers (Moretti, 2004a(Moretti, , 2004b. Furthermore, the local stock of human capital has been found to increase the quality of life in an area (Shapiro, 2006;Winters, 2011a) and lead to future population and employment growth (Glaeser, Scheinkman, and Shleifer, 1995;Simon, 1998Simon, , 2004Simon and Nardinelli, 2002;Winters, 2011b). Given the regional benefits of higher education, increasing the percentage of young people with a college education is an important goal for policymakers, but there is little consensus on how that is best achieved (McHenry, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have suggested that the local stock of human capital in an area creates positive externalities for local labor market outcomes (Rauch 1999;Moretti 2004a,b,c;Shapiro 2006;Iranzo and Peri 2011;Winters 2011aWinters , 2013) and leads to future employment and population growth (Glaeser, Scheinkman and Shleifer 1995;Glaeser and Saiz 2004;Simon 1998Simon , 2004Simon and Nardinelli 2002). 1 In particular, areas with a high percentage of high human capital workers have higher wages, and this is true for both high human capital and low human capital workers and controlling for individual worker characteristics.…”
Section: Introductionmentioning
confidence: 99%